소규모 지방자치단체의 스포츠산업 활성화 전략: 강진군과 남해군의 사례를 중심으로 - 김민철; Min Cheol Kim (Ch'eyuk kwahak yŏn'gu, 2008)
이 연구는 스포츠산업 도시로의 전환에 비교적 성공적인 사례로 평가받고 있는 강진군과 남해군을 대상으로 하였으며, 이들 도시에서의 사례분석을 통해 지역단위가 작은 도시에서의 성공적인 스포츠산업 활성화 전략을 제시하는데 연구의 목적이 있다. 이러한 연구의 목적을 달성하기 위해 현재까지 진행된 스포츠산업의 전반적인 상황분석과 발전가능성에 대한 환경분석(SWOT), 그리고 SWOT matrix전략을 통해 스포츠산업 활성화 전략을 모색하였으며, 그 결과는 다음과 같다. 첫째, 강진군과 남해군의 스포츠산업 관련예산은 지속적으로 증가하고 있으며, 스포츠이벤트와 동계전지훈련 유치를 위한 스포츠시설도 급격히 증가하고 있었다. 또한 축구와 야구, 마라톤 등의 대규모 선수들을 유입할 수 있는 스포츠이벤트를 매년 유치하고, 동계전지훈련 인구도 가파르게 증가하였다. 하지만 스포츠산업과 관련된 종사자 수는 매우 적은 것으로 나타났다. 둘째, 강진군과 남해군의 스포츠산업 환경분석결과 강점요인으로는 지속적인 스포츠산업의 투자, 집약된 스포츠시설, 스포츠이벤트의 활성화, 도시유입인구의 증가로 인한 지역경제활성화로 나타났고, 약점요인으로는 인근도시에 비해 열악한 경제구조, 부족한 관광산업시설, 취약한 도시접근시설, 전·후방 연계산업의 취약 등이 나타났다. 기회요인으로는 스포츠관광 프로그램의 개발, 지방재정의 확대로 인한 지역 재투자, 지자체브랜드 상승효과, 스포츠산업으로 인한 고용창출이 있고, 위협요인으로는 타도시의 스포츠산업 투자확대, 연속성을 가진 스포츠이벤트의 부재, 동계전지훈련의 한정된 참가인원 등으로 나타났다. 셋째, 강진군과 남해군의 스포츠산업 SWOT matrix 분석결과 강점/기회전략은 지속적인 스포츠산업 투자로 인한 지역고용창출유도, 스포츠이벤트와 스포츠관광 프로그램의 연계, 지역경제활성화로 인한 관련 산업의 재투자이며, 강점/위협전략은 지속적 투자를 통한 인근도시의 위험극복, 스포츠시설 및 지역문화를 활용한 스포츠이벤트개최, 다양한 동계전지훈련종목유치로 나타났다. 또한 약점/기회전략으로는 투자유치를 통한 고용 및 취약한 연계산업의 극복, 스포츠산업의 활성화에 따른 간접시설의 개발, 스포츠이벤트와 지자체브랜드로 이어지는 마케팅활동이 있으며, 약점/위협전략으로는 숙박시설의 부족으로 인한 이벤트 개최효과 감소, 인근도시와 경쟁관계 가속화, 제한된 종목의 스포츠이벤트와 동계전지훈련유치로 나타났다. 넷째, 소도시의 스포츠산업 활성화 전략에서 부합전략으로는 스포츠-관광-체험으로 이어지는 스포츠관광 상품의 개발과 지역축제와 연계한 스포츠이벤트 개최이며, 전환전략으로는 방문객의 체계적인 지원서비스 제공 및 차별화된 동계전지훈련 프로그램의 제공, 마지막으로 최소화 전략으로는 스포츠관련 산업의 적극적인 투자유치와 스포츠이벤트를 활용한 지자체의 브랜드 확보이다. The subjects of this study were Gangjin county and Namhae county that they were evaluated as successful cities in switchover to sport industry city. The purpose of this study was to suggest successful sports industry revitalization strategy in small city by analyzing sports marketing cases about two cities. I analyzed a general situation of sports industry and used SWOT to find out the development possibility of cities and tried to find a solution to revitalize sports industry. The result of this study were as follows; First, the budget related to sports industry of Gangjin county and Namhae county have increased steadily, and sports facilities for sports event and winter training inducement rapidly have increased. And, they have attracted sports event that can induce many players or staffs to the autonomous entity such as soccer and baseball, marathon, in their cities people for winter season training have been increased steadily. But number of workers related to sports industry was very few. Second, according to SWOT about sports industry policy of Gangjin county and Namhae county, there are strong factors such as : continuous investment for sports industry, intensive sports facilities, revitalization of sports events, local economy revitalization due to the increase of the population, there are weak factors such as : poor economy structure compared with near cities, lack of tourist industry facilities, uncomfortable transportation system, and lack of related industry. There are opportunity factors such as : development of sports tourist program, reinvestment for the city due to local finance, improving effect of local autonomous system`s brand. At the last, there are threatening factors such as : investment expansion of sports industry about other cities, absent of sports event that can induce other events, limited population that participate in winter season training and so on. Third, according to SWOT matrix analysis of Gangjin county and Namhae county, strong and opportunity strategies were to increase jobs through continuous sports industry investment, to connect sports event with sports tourism program, and to reinvest related industry due to local economy revitalization. Strong and threat strategies were to overcome difficulties of near cities through continuous investment, to hold sports event using of regional culture, and to attract various winter season training event. Weak and opportunity strategies were to increase employment through investment inducement and to overcome difficulties of related industry, to develop subsidiary facilities through sports industry revitalization, to have various marketing activities that were connected with sports event and local autonomous entity brand. And weak and threat strategies were to decrease event effect due to lack of lodging facilities, to accelerate competitive connection with near cities, and to attract limited sports event and winter season training event. Fourth, in sports industry strategies of small cities, correspondence strategies were to develop sports tourism program that let people experience sports, sightseeing, various activities, and to hold sports event that was linked with regional culture. Conversion strategy was to offer systematic support service and differentiated winter season training program. For the last time, minimization strategy was to ensure investment about related sports industry and local autonomous entity brand using of sports event.